THE EFFECT OF ONLINE GUIDED INQUIRY LABORATORY TOWARD STUDENTS’ CRITICAL THINKING ABILITY - Imawati Rohana; Wayan Suana; I Dewa Putu Nyeneng; Kartini Herlina (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
This study aimed to determine the effect of online through guided inquiry laboratory toward students' critical thinking ability. This research was carried out at MAN 1 Central Lampung in the 2021/2022 academic year with a sample consisting of two classes and a total of 64 students. The research design was a one group pre-test post-test design. The experiment was conducted by applying five stages of guided inquiry laboratory learning models, namely observation, manipulation, generalization, verification, and application. The results showed that there were differences in critical thinking ability before and after treatment with an average pre-test value of 30.76 and post-test 56.25 and an average N-Gain of 0.36 in the medium category. The results of hypothesis testing through paired sample t-test obtained sig value. (2-tailed) of 0.000. Thus, it can be concluded that there are positive and significant influence in physics learning through an online guided inquiry laboratory toward students' critical thinking ability.